Synthesis and characterization of quinazoline derivatives: search for hybrid molecule as diuretic and antihypertensive agents. (October 2014) - Rahman, Mujeeb Ur; Rathore, Ankita; Siddiqui, Anees A.; Parveen, Gazala; Yar, M. Shahar
Abstract To explore the pharmacological and structure–activity relationship of a series of N-substituted-(4-oxo-2-substituted-phenylquinazolin-3-(4H)-yl), substituted benzene sulfonamide derivatives (1–25) were synthesized from substituted anthranilic acids derived amino quinazolines and substituted benzene sulphonamides. All the synthesized compounds were evaluated for their diuretic (by Lipschitz et al. method), antihypertensive activity by non-invasive blood pressure (NIBP) using the tail-cuff method and anti-diabetic potential in rats. Six compounds showing significantly excellent activity were compared with metolazone, prazosin and diazoxide as standards. Compound N-[7-chloro-2-(4-methoxyphenyl)-4-oxoquinazolin-3(4H)-yl]-4 nitrobenzenesulfonamide (20) exhibited most potent of the series.